Characteristics of pediatric multiple sclerosis: The Turkish pediatric multiple sclerosis database. (November 2017) - ,; Yaramış, Ahmet; Cansu, Ali; Ünalp, Aycan; Aksoy, Ayşe; Bayram, Ayşe Kaçar; Kartal, Ayşe; Tosun, Ayşe; Serdaroğlu, Ayşe; Konuşkan, Bahadır; Sarıoğlu, Berrak; Yüzbaşı, Beste Kıpçak; et al.
Abstract: Objective: To document the clinical and paraclinical features of pediatric multiple sclerosis (MS) in Turkey. Methods: Data of MS patients with onset before age 18 years (n = 193) were collected from 27 pediatric neurology centers throughout Turkey. Earlier-onset (<12 years) and later-onset (≥12 years) groups were compared. Results: There were 123 (63.7%) girls and 70 (36.3%) boys aged 4–17 years, median 14 years at disease onset. Family history of MS was 6.5%. The first presentation was polysymptomatic in 55.4% of patients, with brainstem syndromes (50.3%), sensory disturbances (44%), motor symptoms (33.2%), and optic neuritis (26.4%) as common initial manifestations. Nineteen children had facial paralysis and 10 had epileptic seizures at first attack; 21 (11%) were initially diagnosed with acute disseminated encephalomyelitis (ADEM). Oligoclonal bands were identified in 68% of patients. Magnetic resonance imaging revealed periventricular (96%), cortical/juxtacortical (64.2%), brainstem (63%), cerebellum (51.4%), and spinal cord (67%) involvement. Visual evoked potentials (VEP) were abnormal in 52%; serum 25-hydroxyvitamin D levels were low in 68.5% of patients. The earlier-onset group had a higher rate of infection/vaccination preceding initial attack, initial diagnosis of ADEM, longer interval between first 2 attacks, and more disability accumulating in the first 3 years of the disease. Conclusion: Brainstem and cerebellum are common sites of clinical and radiological involvement in pediatric-onset MS. VEP abnormalities are frequent even in patients without history of optic neuropathy. Vitamin D status does not appear to affect the course in early disease. MS beginning before 12 years of age has certain characteristics in history and course. Highlights: This study confirms pediatric MS is a predominantly relapsing-remitting disease. Brainstem-cerebellar or ADEM-like symptoms, facial paralysis, seizures are frequent. Onset with sensorial symptoms is less likely compared to later-onset MS. High rates of vitamin D deficiency and subclinical VEP abnormalities are of note. First inter-attack interval is longer, disability accumulates faster in early-onset MS.